Effect of annealing temperature on β-Ga2O3 thin films deposited by RF sputtering method - Singh, Amit Kumar; Gupta, Mukul; Sathe, V.; Katharria, Y.S. (Superlattices and microstructures, 2021)
In this work, Gallium oxide (Ga2O3) films were deposited by RF magnetron sputtering on quartz and n-type Si (100) substrates at room temperature. The effect of annealing temperature on crystalline structure and band gap of β-Ga2O3 thin films were investigated in detail. X-ray diffraction revealed the formation of monoclinic polycrystalline thin films. The bandgap of the thin films was estimated to be in the range of 4.75 eV–5.15 eV. Raman spectra indicated blue and red shifts of Ga2O3 phonon modes in the thin films. The absorption bands at 647.05 cm−1 due to vibrations of Ga–O bonds were identified through Fourier-transform infrared spectroscopy. •Effects of thermal annealing on structural & optical properties of RF sputtered gallium oxide thin films are investigated.•XRD, Raman and FTIR observations confirm the formation of the monoclinic β-Ga2O3.•Optical bandgap widens with increasing annealing temperature due to suppression of defect-related states present in bandgap.•Raman modes of Ga2O3 show blue and red shift due to a significant change in ordering of oxygen atoms around gallium atoms.